KAJIAN PENGARUH SUHU UDARA PENGERING DAN TEKANAN UDARA NOZZLE TERHADAP SIFAT FISIK SUSU BUBUK PADA PROSES PENGERINGAN DENGAN SPRAY DRYER - , OLIVIA SITADEWI; , Dr. Joko Nugroho, WK., STP., M.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Fresh milk is a food that is highly nutritious because they contain substances that complete and balanced food like protein, fats, carbohydrates, minerals, and vitamins that are needed by humans. To extend the storage period of milk, fresh milk is converted into milk powder by drying. Spray dryer is one form of drying that has been widely applied in the milk processing industry. High-temperature of drying which will produces powder with low moisture content and the amount of powder that is much more. This research aims to analyze the condition of drying air temperature and air pressure nozzle for optimum milk powder drying process. Whole milk with solids content of 12% weighed 2,000 grams. To obtain optimum drying conditions to analyze the effect of drying air temperature and air pressure nozzle on the quality of powder which includes the final moisture content, bulk density, degree of whiteness, wettability and angle of repose and production efficiency. Variations in air pressure nozzle used is 1 kg/cm2, 2 kg/cm2, and 3 kg/cm2 and drying air temperature variations is 240oC, 250oC, and 260oC. The result is the drying air temperature increase causes a decrease in the final moisture content, bulk density and production efficiency. While the increase of air pressure nozzle causes an increase in water content, bulk density and production efficiency. The optimal temperature is obtained at a temperature 250oC and pressure of 2 kg/cm2 air nozzle based on the value of water content.